IMPLEMENTASI PROGRAM POSYANDU LANSIA DALAM MENINGKATKAN KESEHATAN LANSIA DI DESA SUMORAME - Farah Rifki Azmi Mauludi; Isnaini Rodiyah (Jurnal Ilmu Sosial dan Ilmu Politik Malikussaleh (JSPM), 2026)
This study examines the implementation of the Elderly Health Center Program in Sumorame Village, Candi District, Sidoarjo Regency, using George C. Edwards III's policy implementation theory as the basis for analysis. The purpose of this study is to determine how the implementation of the Elderly Health Center Program improves the health of the elderly in Sumorame Village. The research method used was a qualitative approach with descriptive analysis, using George C. Edwards III's (1980) policy implementation theory, which involves four main indicators, namely communication, resources, disposition, and bureaucratic structure. The results showed that program communication was quite effective, as indicated by the clear and consistent delivery of information through WhatsApp groups and physical letters. However, there were obstacles in terms of resources, such as limited health workers, inadequate infrastructure, and a lack of formal training for new cadres, even though budget support from the village government increased every year. In terms of disposition, the implementers showed high dedication and commitment, while the bureaucratic structure did not yet have written Standard Operating Procedures (SOPs). The findings emphasize the importance of improving the quality of resources, providing more comprehensive facilities, and developing standard operating procedures so that the program runs in a more focused and sustainable manner. In addition, cross-sector collaboration and family involvement are important factors in realizing healthy, independent, and productive elderly people.